2016 South Florida Beef Forage Survey Results - Laura Bennett; Bosques Jonael; Sarah Bostick; Lauren Butler; Sonja Crawford; Taylor Davis; Christa Kirby; Colleen Larson; Philipe Moriel; Chris Prevatt; Brent Sellers; Maria Silveira; et al. (EDIS)
This publication discusses a survey used to evaluate ranch management practices to determine benchmarks in cattle production and pasture management. Written by Laura Bennett, Jonael Bosques, Sarah Bostick, Lauren Butler, Sonja Crawford, Taylor Davis, Christa Kirby, Colleen Larson, Philipe Moriel, Chris Prevatt, Brent Sellers, Maria Silveira, Aaron Stam, Bridget Stice, Joao Vendramini, and Lindsey Wiggins, and published by the UF/IFAS Agronomy Department, July 2021.